Papular-purpuric gloves and socks syndrome. - Bonifazi, E. (European Journal of Pediatric Dermatology, 2015)
Papular-purpuric gloves and socks syndrome is an immune-mediated vasculitis due to a viral infection, usually caused by Parvovirus B19 (1), but sometimes also by other viruses, such as human herpes virus 6 and cytomegalovirus. Parvovirus B19 infection has an incubation period of 6 days, has as target the bone marrow erythrocyte progenitor and can cause bone marrow aplasia in patients with decreased erythrocyte half-life - servere anemia, AIDS - (2). Clinical manifestations, which are usually absent or mild and non-specific, can appear 2 weeks after the contagion and manifest themselves in children as erythema infectiosum (fifth disease) and in adolescents and young adult as papular-purpuric gloves and socks syndrome; in pregnant women during the first trimester the infection can be responsible for abortion. The etiological diagnosis is done by searching for specific IgM in serum or, in immunocompromised patients, for virus DNA.